Screening of β -damascenone-producing strains in light-flavor Baijiu and its production optimization via response surface methodology - Tang, Jie; Lin, Bin; Jiang, Wei; Li, Qun; Zhu, Liping; Zhang, Gang; Chen, Qianjin; Yang, Qiang; Yang, Shengzhi; Chen, Shenxi (Frontiers in Microbiology, 2022)
As a C13-norisoprenoid aroma substance, β-damascenone is a highly important aromatic compound and an active constituent. The purpose of this study was to investigate the change law of β-damascenone during the light-flavor Baijiu brewing process, and screen the indigenous microbial strains that produce this compound and optimize fermentation parameters for improving β-damascenone production using a statistical approach. In this project, Wickerhamomyces anomalus YWB-1 exhibited the highest producing activity of β-damascenone. Fermentation conditions were optimized for β-damascenone production using a one-factor-at-a-time approach. A Plackett-Burman design was subsequently adopted to assess the effects of initial pH, incubation temperature, inoculum size, fermentation period, and original Brix degree. Analysis of variance showed that the correlation coefficient (R2) of the executive model was 0.9795, and this value was significant (p < 0.05). Three significant variables were optimized at three different coded levels using a Box‒Behnken design of response surface methodology (RSM). Here, 7.25 μg/L β-damascenone was obtained under the following optimum conditions: initial pH of 3.31, original Brix degree of 10.53%, and fermentation period of 52.13 h. The yield was increased 3.02-fold compared with that obtained under unoptimized conditions. This information is conducive to the control of flavor production by regulating variable parameters in Baijiu fermentation.